THE ANALYSIS OF MOBILE BANKING ACCEPTANCE FOR TRADITIONAL PRIVATE BANK CUSTOMERS IN INDONESIA - Rachmawati, Patricia; Lukman, Hendro (Graduate Program of Universitas Tarumanagara, 2024)
Many banks have improved digital customer service through mobile banking, including private banks and government banks. The development of mobile banking in Indonesia is very massive, starting with the COVID-19 pandemic. However, not all customers want to take full advantage of mobile banking. This research aims to analyze the factors that influence mobile banking adoption. The subjects of this research are private customers aged over 20 years. Research that uses primary data by distributing questionnaires with the variables Perceived Usefulness and Perceived East to Use with Attitude as a mediating variable. Data collection used the convenience method and continued with the snowball method. A valid questionnaire was used by 99 respondents, then analyzed using path analysis. The research results show that perceived usefulness influences mobile banking adoption, but is different from Perceived Ease to Use. The conclusions obtained from this research indicate that customers have felt the benefits of mobile banking, but customers still need effort or are not yet comfortable in operating it. The implication of this research is that banks still have to develop mobile banking systems or applications in order to simplify mobile banking operations according to the characteristics and conditions of their customers.